The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/feart.2021.604930
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Mapping of Methane Concentrations at the Bush Hill Hydrocarbon Seep, Gulf of Mexico

Abstract: The role of methane as a green-house gas is widely recognized and has sparked considerable efforts to quantify the contribution from natural methane sources including submarine seeps. A variety of techniques and approaches have been directed at quantifying methane fluxes from seeps from just below the sediment water interface all the way to the ocean atmosphere interface. However, there have been no systematic efforts to characterize the amount and distribution of dissolved methane around seeps. This is critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…In the two erosion craters, the ROV sonar survey showed that bubbles were released from several individual vents (Figure 7). Similar venting has been reported from natural seeps (De Beukelaer et al, 2003;Johansen et al, 2014;Sahling et al, 2016;Johansen et al, 2020;Meurer et al, 2021). Under such circumstances, bubble density would be locally variable.…”
Section: Discussion Of Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In the two erosion craters, the ROV sonar survey showed that bubbles were released from several individual vents (Figure 7). Similar venting has been reported from natural seeps (De Beukelaer et al, 2003;Johansen et al, 2014;Sahling et al, 2016;Johansen et al, 2020;Meurer et al, 2021). Under such circumstances, bubble density would be locally variable.…”
Section: Discussion Of Resultssupporting
confidence: 74%
“…Hu et al (2012), who collected pumped water samples from the surface interface, failed to confirm this result at Bush Hill and a second ~1,000 m seep. Meurer et al (2021), sampling with MET sensors deployed on gliders over Bush Hill, measured methane concentrations of up to 0.4 μM/L, well below the observations of Solomon et al (2009). Notably, results from the work of Yvon-Lewis et al (2011), using techniques to similar to those used by Hu et al (2012) and Ryerson et al (2011), using airborne measurements, suggested that oil reaching the surface (~3,000 m 3 /d) from the Deepwater Horizon oil spill, which leaked from 4,500 m depth, was a negligible source of methane to air.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The model can be used to predict assuming oil droplets only, oil-coated gas bubbles only, or both droplets and bubbles. For example, ADCP profiles of the water column above the Bush Hill seep, north-central Gulf of Mexico (Meurer et al, 2021), can be used to model the expected OSO locations for the time period represented by the data (Figure 9A, 9B). The spread of model OSOs uses the bounding ADCP profiles for each day and allows a 35% correlated, relative standard deviation for the Monte Carlo simulations.…”
Section: Evaluation Of Oso Offset From Seepmentioning
confidence: 99%
“…However, the Pro Oceanus Mini Pro CO2 sensor used at the time did not withstand the pressure changes imposed by glider missions. The Franatech METS CH4 sensor has been integrated into Alseamar SeaExplorer and Teledyne Slocum gliders and successfully used to generate concentration maps of a methane seep in a semi-quantitative way (Meurer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%